(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research investigates how artificial intelligence (AI) might improve computerized customer support relationships. To differentiate between welcomed and unwelcoming online buying habits, it applies an organism-based approach based on the Stimulus-Organism-Response concept and views artificial intelligence programs as such. AI is capable of analysing consumer data and producing reactions that change connections. The Introduction of AI and internet marketing has had a profound effect on the world the financial situation, and It is predicted that AI will be used extensively in communications and selling. It may predict customer attitudes, facilitate analysis of information, and provide ideas for fresh goods.